Nonenzymatic RNA copying with a potentially primordial genetic alphabet - Ziyuan Fang; Xiwen Jia; Yanfeng Xing; Jack W. Szostak (Proceedings of the National Academy of Sciences, 2025)
Nonenzymatic RNA copying is thought to have been responsible for the replication of genetic information during the origin of life. However, chemical copying with the canonical nucleotides (A, U, G, and C) strongly favors the incorporation of G and C and disfavors the incorporation of A and especially U because of the stronger G:C vs. A:U base pair and the weaker stacking interactions of U. Recent advances in prebiotic chemistry suggest that the 2-thiopyrimidines were precursors to the canonical pyrimidines, raising the possibility that they may have played an important early role in RNA copying chemistry. Furthermore, 2-thiouridine (s 2 U) and inosine (I) form by deamination of 2-thiocytidine (s 2 C) and A, respectively. We used thermodynamic and crystallographic analyses to compare the I:s 2 C and A:s 2 U base pairs. We find that the I:s 2 C base pair is isomorphic and isoenergetic with the A:s 2 U base pair. The I:s 2 C base pair is weaker than a canonical G:C base pair, while the A:s 2 U base pair is stronger than the canonical A:U base pair, so that a genetic alphabet consisting of s 2 U, s 2 C, I, and A generates RNA duplexes with uniform base pairing energies. Consistent with these results, kinetic analysis of nonenzymatic template-directed primer extension reactions reveals that s 2 C and s 2 U substrates bind similarly to I and A in the template, and vice versa. Our work supports the plausibility of a potentially primordial genetic alphabet consisting of s 2 U, s 2 C, I, and A and offers a potential solution to the long-standing problem of biased nucleotide incorporation during nonenzymatic template copying.